IN VIVO ANTI-INFLAMMATORY ACTIVITY OF DADAP LEAVES (Erythrina subumbrans (Hassk.) Merr) - Ni Luh Kade Arman Anita Dewi; Ni Luh Sintya; Maria Malida Vernandes Sasadara; Erna Cahyaningsih; Putu Era Sandhi Kusuma Yuda; Puguh Santoso (International Journal of Biosciences and Biotechnology, 2021)
Leguminosae is widely known for its anti-inflammatory properties due to the presence of several beneficial phytochemicals, including alkaloids, flavonoids, steroids, and saponins. Dadap (Erythrina subumbrans (Hassk.) Merr), a Leguminosae member, has empirically been used to treat inflammation. This research aimed to prove the anti-inflammatory effect of Dadap leaves scientifically. Dadap leaves were macerated in 96% ethanol to produced crude ethanol extract, followed by in vivo anti-inflammatory assay with the paw edema method. Three different doses of extract: 200, 300, and 400mg/kg BW, were administrated to Wistar rats to observed its ability in reducing carrageenan-induced inflammatory. All extract doses produced similar anti-inflammatory activity as compared to diclofenac sodium as a positive control. There is no significant difference among the three different doses. The results indicated that all treatment doses produced anti-inflammatory activity, but 200mg/kg BW administration was most efficient.